2000
DOI: 10.2337/diacare.23.6.813
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of 125I-labeled insulin glargine (HOE 901) in healthy men: comparison with NPH insulin and the influence of different subcutaneous injection sites.

Abstract: Abbreviations: ANCOVA, analysis of covariance; ANOVA, analysis of variance; IRI, immunoreactive insulin; NEFA, nonesterified fatty acid; T 75% , time in hours for 25% of the administered radioactivity to disappear after bolus subcutaneous injection.A table elsewhere in this issue shows conventional and Système International (SI) units and conversion factors for many substances. Pharmacokinetics of 125 I-Labeled Insulin Glargine (HOE 901) in Healthy MenComparison with NPH insulin and the influence of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(106 citation statements)
references
References 5 publications
6
99
0
1
Order By: Relevance
“…[1][2][3][4] This may make it difficult to achieve stable glycemic control over 24 hours, as both the variability and pronounced peak can result in unexpected hyperglycemia or hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] This may make it difficult to achieve stable glycemic control over 24 hours, as both the variability and pronounced peak can result in unexpected hyperglycemia or hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…41 Compared with NPH insulin, insulin glargine is characterized by a smoother, relatively flat, GIR curve ( figure 2). There appears to be little or no difference in the absorption rate of insulin glargine between various subcutaneous injection sites (e.g., arm, leg, abdomen), 37 nor was absorption adversely affected by 30 minutes of intense exercise. 42 Euglycemic clamp data gathered with insulin detemir in subjects with type 1 diabetes revealed a duration of action of 19.9 hours for a typical dose of 0.4 units/kg.…”
Section: Rapid-acting Analogsmentioning
confidence: 99%
“…9 Pharmacokinetic/pharmacodynamic studies have confirmed that, compared to NPH insulin, both long-acting analogs have a more prolonged and consistent duration of action, without the marked post-injection peak characteristic of NPH insulin. [34][35][36][37][38] Duration of action is most reliably measured through euglycemic clamp studies in patients with type 1 diabetes, rather than in healthy subjects or those with type 2 diabetes, because of the confounding influence of endogenous insulin secretion. 39 Studies of this nature with insulin glargine have reported a duration of action of 20 to 24 hours after single dose administration 35,36,40 and 24 to 25.6 hours at steady-state.…”
Section: Rapid-acting Analogsmentioning
confidence: 99%
“…23 NPH insulin, for example, is characterised by a peak in the pharmacokinetic profile 4-6 h after injection followed by a steady decline, rather than a low and constant absorption. 25 The combination of a peak in effect and the unpredictability of the time and extent of this peak inevitably incurs a risk of hypoglycaemia, and as basal insulins are often dosed in the evening there is a real risk of nocturnal hypoglycaemia. This limits the tolerable dose and has led to the search for basal insulin analogues with improved pharmacokinetic and pharmacodynamic properties.…”
Section: The Rationale For a Basal Insulin Analoguementioning
confidence: 99%
“…27,28 Nevertheless, this principle was successfully used in later years to produce insulin glargine (Gly A21 Arg B31 Arg B32 human insulin), in which two arginine residues added to the C-terminus of the B-chain shift the isoelectric point from pH 5.4 to 6.7. 25,29 A second strategy aimed at producing an improved basal insulin was to engineer a stable hexamer by substituting the zinc ions situated in the core of the hexameric structure with cobalt ions. 30,31 This complex, named Co(III)insulin, was found to be absorbed slowly as a hexamer and then undergo enzymatic cleavage into monomers in the circulation.…”
Section: The Rationale For a Basal Insulin Analoguementioning
confidence: 99%